The problem of V. N. Dubinin for symmetric multiconnected domains - Zabolotnii , Ya. V. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.54 We consider a quite general problem from the geometric theory of functions on finding a maximal value of the product of the inner radii of n non-overlapping domains, which contain points of the unit circle and are symmetric with respect to the unit circle, and the γ-powered inner radius of a domain containing the origin. In this paper, we solve this problem for n≥ 20 and 1<γ≤ n^23-q(n).